Divine simplicity in the theology of Irenaeus - Simons, Jonatán (Vigiliae Christianae, 2023)
"This book focuses on Irenaeus as key to the early Christian appropriation of divine simplicity as a philosophical principle, since he is the first Christian source to explain his usage in relation to God. Beyond providing limits for what a simple God can and cannot mean, he also applies this principle to God's activity (i.e. creating), and to God's names and powers. There is a growing interest in the early Christian appropriation of divine simplicity: Simons' study is timely as the first book to focus exclusively on the earliest explanation and application"--